Implications of the shift of the responsibility for career development on International Human Resource Management practices - Blazevic, Danijela (My University, 2012)
The responsibility over career development has been shifting from the organization to the individual influencing International Human Resource Practices. The various trends in the economy, demography, and technology supported the shift. While there have been researches on the changing nature of the career, transforming careers, new career models, future of the career development, the research about the shift of the responsibility for career development and its influence on the IHRM practices has not been found. Therefore, the research question examines the impact of the reported shift of responsibility for career development from organization to individual on four international human resource management practices: staffing, training and development, compensation and benefits and expatriation. Special attention is paid on the expatriation management due to the discussion boundaryless careerist. To complete this research, the qualitative method was applied. Nine in-depth semi structured interviews were conducted with the Human Resource Managers and Team Leaders in six companies. The main findings of the research indicate that organization takes responsibility for development of the top talented people rather than all employees. The organization expects non talented individuals to be developed by themselves while the individuals are still expecting organization to take responsibility but they start to realize that they have to take the responsibility for the career development. In addition, the organization does not need to invest or implement total reward system for the boundaryless careerists since the relationship is based on the contract fulfilment and pay. Consequently, organization does not have concerns about retention nor repatriation.
Keywords: IHRM; career development; boundaryless career; expatriation; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|